The impact of perceived website quality on customer satisfaction in Kuala Lumpur, Malaysia - Tiong, Li Li (2019)
The rapid growth of internet around the world has opened new marketplace and revolutionized the process of buying and selling goods. As a result, online purchasing or shopping is developed for better shopping convenience. However, to continuously sustain the online business, business organizations have faced many new challenges in satisfying the needs of their customers who are increasingly expecting higher quality services, more time saving, more online security, and more convenience. From the previous literature, website quality has been recognized as an important indicator of customer satisfaction. This study considered five website quality factors which include aesthetics and marketing mix (referring to content of the website), usability and interactivity (referring to functionality of the website) and online trust (psychological factor). This study applied a quantitative cross-sectional approach to investigate the perception of online shoppers on website quality in accordance to the five factors, and subsequently examine their respective impact on customer satisfaction. This study considered a total of 385 samples from 11 districts in Kuala Lumpur. A closed-ended questionnaire is created using Google Form platform for data collection and the samples are collected utilizing non-probability quota sampling technique. From the findings, it is revealed that online shoppers in Kuala Lumpur, Malaysia are expressing a positive perception towards the five website quality factors and online satisfaction. It is also revealed that each website quality factor is significantly correlated with customer satisfaction. In this aspect, online trust factor demonstrated the strongest while aesthetics factor showed the weakest correlation with customer satisfaction. More importantly, when all the five quality factors are applied as a group, online trust factor is found to be the strongest predictor while usability is the weakest predictor of customer satisfaction. The findings presented in this study can provide an evaluation of the extent to which the content, functional and psychological factors of the website are meeting the online consumers’ demand. The knowledge obtained is helpful to online vendors in understanding their current position against competitors, identify their weaknesses and subsequently address the key factors affecting consumer’s purchasing behaviour that can potentially help them to retain existing customers and attract new online shoppers.